Durkheim and the Jews of France - Strenski, Ivan. (Chicago, Ill. : University of Chicago Press, 1997)
Ivan Strenski debunks the common notion that there is anything "essentially" Jewish in Durkheim's work. Seeking the Durkheim inside the real world of Jews in France rather than the imagined Jewishness inside Durkheim himself, Strenski adopts a Durkheimian approach to understanding Durkheim's thought. In so doing he shows for the first time that Durkheim's sociology (especially his sociology of religion) took form in relation to the Jewish intellectual life of late nineteenth- and early twentieth-century France. Strenski begins each chapter by weighing particular claims (some anti-Sem.
Includes bibliographical references (pages 161-202) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Durkheim, Émile, -- 1858-1917.; Durkheim, Émile, -- 1858-1917; Jews -- France -- Intellectual life; France -- Intellectual life -- 19th century; France -- Intellectual life -- 20th century; France -- Ethnic relations; Juifs -- France -- Vie intellectuelle; France -- Vie intellectuelle -- 19e siècle.; France -- Vie intellectuelle -- 20e siècle.; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Ethnic relations; Intellectual life; Jews -- Intellectual life; France; 1800-1999